2020
DOI: 10.1200/jco.2020.38.15_suppl.5006
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of nivolumab and salvage nivolumab + ipilimumab in treatment-naïve patients (pts) with advanced renal cell carcinoma (RCC) (HCRN GU16-260).

Abstract: 5006 Background: Nivolumab (nivo) is FDA approved for pts with VEGFR TKI-resistant RCC and the nivo + ipilimumab (nivo/ipi) combination is FDA approved for treatment naïve pts with IMDC intermediate and poor risk RCC. Little information is available on the efficacy and toxicity of nivo monotherapy in treatment naïve RCC or the efficacy of nivo/ipi salvage therapy in pts with tumors resistant to initial nivo monotherapy. Methods: Eligible pts with treatment naïve RCC received nivo 240mg IV q2 wk x 6 doses foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 0 publications
3
39
1
3
Order By: Relevance
“…However, only a minority of patients could be rescued by the addition of ipilimumab at the time of disease progression. 32 Hence, compromising drug exposure in the initial treatment phase when an ICI/ICI combination is chosen needs careful balancing.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a minority of patients could be rescued by the addition of ipilimumab at the time of disease progression. 32 Hence, compromising drug exposure in the initial treatment phase when an ICI/ICI combination is chosen needs careful balancing.…”
Section: Discussionmentioning
confidence: 99%
“…A different treatment strategy based on individual response to upfront ICI monotherapy is being explored (HCRN GU16-260, OMNIVORE) by allowing treatment interruption to responders while adding other ICI as salvage treatment to non-responders (10,11). Preliminary results in patients with treatment-naïve clear cell mRCC demonstrated some activity of ICI monotherapy with an observed ORR of 29% in the HCRN GU16-260 trial and 12% at 6 months in the OMNIVORE study, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a single-arm phase 2 study (KEYNOTE-427), the PD-1 inhibitor pembrolizumab has shown encouraging antitumor activity in patients with treatment-naïve mRCC with both clear cell and non-clear cell histology (8,9). Two different phase 2 studies (HCRN GU16-260; OMNIVORE) testing nivolumab followed by salvage ipilimumab in patients with clear cell mRCC have also shown clinical activity of nivolumab monotherapy in this setting (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Исследований эффективности ниволумаба в 1-й линии лечения в монорежиме, а также последовательной иммунотерапии в настоящее время недостаточно. Поэтому представляются интересными предварительные результаты исследования II фазы по изучению эффективности ниволумаба у больных ПКР в 1-й линии терапии, а также по целесообразности добавления ипилимумаба в случае прогрессирования заболевания на фоне монотерапии [10].…”
Section: рис 4 общая выживаемость (а) и выживаемость без прогрессирunclassified